Mass transpiration impact on effectiveness of heat transport of ternary hybrid nanofluid with velocity slip - S. Bilal; Muhammad Yasir (Case Studies in Thermal Engineering)
Admirable utilizations about the dynamical movement of rheological materials over exponentially shrinking configurations in industrial and technological fields have mesmerized investigators. Some potential applications are in polymer processing, fiber production, power generation, refrigeration, aircraft design, and many more. Furthermore, to raise the efficiency and to optimize the performance of the aforementioned mechanisms insertion of the composition of distinctively natured ternary nanoparticles comprising of Cu, TiO2 and Ag are induced. Water is considered as base liquid and its flow due to stretchable/shrinkable surface is entertained. The effectiveness of permeable medium by accounting modified Darcy law to envision inertial aspects is included. Thermal energy transmission in the emergence of radiative flux and variant heat source through non-linear approximating function is also manifested. The velocity boundary constraint with suction is applied at the boundary of the surface to examine the change in fluid motion. Translation of governing equations in the form of ordinary differential setup after execution of a similar approach is applied. BVP4C solver is capitalized to resolve the problem and run simulation relevant to shrinking/stretching case for upper and lower branches of the solution. Associated quantities concerned with momentum and heat flux are enumerated for a vast range of parameters. It is inferred from the comprehensive and in-depth analysis of attained outcomes that convective heat transfer determined through Nusselt number elevates versus suction and radiation parameters. Furthermore, the implication of externally applied magnetic field and suction causes the opposite i.e. increasing and decreasing impact on velocity distribution respectively for first and second-branch solutions. Radiation and variable heat sources exclusively raise the temperature distribution in all situations.